Shengqingjiangzhuo Capsules Alleviates Renal Fibrosis by Targeting Glomerular Endothelial Cells Exosome miR ‐31‐5p/ HO ‐1 to Suppress Tubular Epithelial Cells Ferroptosis - Feng Pan; Jinhong Lu; Gaxi Ye; Haifeng Zhu; Hongyuan Ma; Jiale Li; Xingyu Yang; Hongtao Yang; Anrong Tong (Clinical and Experimental Pharmacology and Physiology, 2026)
ABSTRACT Objective Chronic renal failure (CRF) represents the advanced stage of chronic kidney disease, for which no specific pharmacological treatments are currently available. Traditional Chinese medicine has demonstrated notable efficacy in managing CRF. Shengqingjiangzhuo capsules (SQJZ capsules), a traditional Chinese medicinal formulation, are employed clinically in the treatment of CRF. However, the precise mechanisms underlying its therapeutic effects remain insufficiently understood. Methods The SQJZ capsule's chemical components were identified using UPLC‐Q‐Exactive‐Orbitrap‐MS. TGFβ1‐induced GECs and adenine‐induced CRF models in mice were developed. Exosome miRNA sequencing, quantitative polymerase chain reaction (qPCR), Western blot and dual‐luciferase reporter assays explored the interaction between miR‐31‐5p and HO‐1, and their effects on ferroptosis markers (ROS, GSH, MDA, Fe 2+ , SLC7A11, GCLC), mitochondrial membrane potential and fibrosis markers α‐SMA and collagen I. Results This study is the first to employ UPLC‐Q‐Exactive‐Orbitrap‐MS technology to analyse SQJZ capsules, identifying 82 active components. It indicates that TGF‐β1‐stimulated GECs‐derived exosomes increase miR‐31‐5p in TECs, causing HO‐1 inhibition and ferroptosis. The active drug in SQJZ capsules serum counteracts these effects, suggesting anti‐ferroptosis and anti‐fibrosis properties and improving renal function in cell and CRF animal models. Overall, SQJZ capsules reduce renal fibrosis by modulating the miR‐31‐5p/HO‐1 axis and inhibiting ferroptosis in TECs. Conclusion SQJZ capsules is associated with amelioration of renal fibrosis by suppressing GECs‐derived exosomal miR‐31‐5p, which derepresses HO‐1 expression in TECs, thereby inhibiting ferroptosis and subsequent renal fibrosis.